2002
DOI: 10.1021/jf025683b
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Antioxidant Activity of Wine Byproducts and Its Correlation with Polyphenolic Content

Abstract: It has been demonstrated that wine and other products derived from the grape have a high antioxidant capability; as a possible consequence of this, they may have potential benefits for health. The byproducts of the winemaking process represent a source of antioxidant compounds that has been relatively unexploited to date, but that is now the subject of increasing industrial interest. This article describes an approach to the study of the antioxidant activity of grape marcs, stalks, and dregs of both white and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

22
173
0
11

Year Published

2008
2008
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 256 publications
(224 citation statements)
references
References 15 publications
(15 reference statements)
22
173
0
11
Order By: Relevance
“…Utilizando-se o método ABTS em nosso estudo, o coeficiente de regressão r 2 entre o conteúdo de fenólicos totais e a atividade antioxidante foi de 0,9199 e 0,9817 para as variedades Ancelota e Tannat, respectivamente. Esses valores confirmam os dados apresentados por diversos estudos, mostrando que a capacidade antioxidante é dependente do teor de compostos fenólicos presentes ( ALONSO et al, 2002;GUENDEZ et al, 2005a; GÓMEZ-PLAZA; MIÑANO; Tabela 2. Antocianinas totais de extratos de bagaço de uva* (g.100 g -1 peso seco) 1 .…”
Section: Atividade Antioxidante E Poder Redutorunclassified
See 2 more Smart Citations
“…Utilizando-se o método ABTS em nosso estudo, o coeficiente de regressão r 2 entre o conteúdo de fenólicos totais e a atividade antioxidante foi de 0,9199 e 0,9817 para as variedades Ancelota e Tannat, respectivamente. Esses valores confirmam os dados apresentados por diversos estudos, mostrando que a capacidade antioxidante é dependente do teor de compostos fenólicos presentes ( ALONSO et al, 2002;GUENDEZ et al, 2005a; GÓMEZ-PLAZA; MIÑANO; Tabela 2. Antocianinas totais de extratos de bagaço de uva* (g.100 g -1 peso seco) 1 .…”
Section: Atividade Antioxidante E Poder Redutorunclassified
“…A atividade antioxidante foi determinada pelos métodos ABTS, FRAP e β-caroteno/ácido linoléico. (ALONSO et al, 2002;LOULI;RAGOUSSIS;MAGOULAS, 2004;KAMMERER et al, 2005;PINELO et al, 2005). Outras partes do conjunto da uva são rejeitadas durante o processo de vinificação, como os engaços, e recebem muito menos atenção, embora contenham uma quantidade importante de polifenóis (SOUQUET et al, 2000).…”
Section: Introductionunclassified
See 1 more Smart Citation
“…Recent studies have underlined the importance of the wine industry by-products as plant materials that are particularly rich in polyphenols with a variety of biological activities (Alonso et al, 2002;Xia et al,2010).…”
Section: Introductionmentioning
confidence: 99%
“…Studies on the chemical composition of the grape pomace revealed its high content of proteins, fibres, sugars, fats, minerals, vitamins and in particular the phenolic compounds (Alonso et al, 2002;Bonilla et al, 1999;Aslanian et al, 2011;Pop et al, 2014) which justify the use of this by-product in animal nutrition (Baumgärtel et al, 2007;Zalikarenab et al, 2007).…”
Section: Introductionmentioning
confidence: 99%